Behavioural variety of a node-based sensorimotor-to-motor map. (December 2020) - Woolford, Felix MG; Egbert, Matthew D
The iterant deformable sensorimotor medium (IDSM) is a controller that has been used to study habits construed as self-sustaining patters of sensorimotor activity. To understand the dynamics of this controller, we investigate a heavily simplified variation of it called a node-based sensorimotor-to-motor map (NB-SMM). This deterministic, stateless, continuous-time controller coupled to a minimalistic robot and environment demonstrates six distinct categories of behaviour, including an ability to distinguish between the two sides of a symmetric stimulus, suggesting that controllers based purely on sensorimotor-state to motor mappings may be more capable than intuition first suggests. As the number of nodes increases, the potential behavioural complexity also increases. With two nodes, cycles become possible, along with systems which produce multiple behaviours depending upon initial conditions. This hints at the potential behavioural complexity of a system with many more nodes and provides insight into the kinds of behaviours that might be accomplished by IDSM-controlled robots or virtual agents.